2014
DOI: 10.1080/21642850.2014.913487
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning, depression, and HIV medication adherence in India: a randomized pilot trial

Abstract: Objective: India is home to the third-largest number of people living with HIV in the world, and no-cost antiretroviral therapy (ART) has been available across the country since 2004. However, rates of adherence to ART are often subpar in India, and interventions to increase adherence are warranted. Cognitive impairment and depression have been associated with ART non-adherence, and may also limit the impact of behavioral interventions designed to improve adherence. Studies have not evaluated the impact of cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Our results emphasized the impact of NCI, as it showed the main effect on ART adherence. Consistent with previous findings, our study showed the significant effect of the presence and severity of NCI on decreased ART adherence (Cook et al, 2014; Hinkin et al, 2002; Malee et al, 2009; Waldrop-Valverde, Jones, Weiss, Kumar, & Metsch, 2008). This finding was significant for HIV-infected individuals, particularly PWUDs, who had a greater likelihood of being cognitively impaired, exhibiting depressive symptoms, and reduced social support due to disease process, lifestyles, and chronic substance use behaviors (Bhatia, Hartman, Kallen, Graham, & Giordano, 2011; Scheyett et al, 2010; Zahari et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Our results emphasized the impact of NCI, as it showed the main effect on ART adherence. Consistent with previous findings, our study showed the significant effect of the presence and severity of NCI on decreased ART adherence (Cook et al, 2014; Hinkin et al, 2002; Malee et al, 2009; Waldrop-Valverde, Jones, Weiss, Kumar, & Metsch, 2008). This finding was significant for HIV-infected individuals, particularly PWUDs, who had a greater likelihood of being cognitively impaired, exhibiting depressive symptoms, and reduced social support due to disease process, lifestyles, and chronic substance use behaviors (Bhatia, Hartman, Kallen, Graham, & Giordano, 2011; Scheyett et al, 2010; Zahari et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…12 studies described counseling interventions that were delivered to individuals, groups, or combined individual and group sessions [ 47 52 , 54 , 56 58 , 60 , 61 ]. Two studies were conducted among adolescents only [ 58 , 60 ], two among both adults and adolescents [ 50 , 61 ], and eight among adults only [ 47 49 , 51 , 52 , 54 , 56 , 57 ]. Three additional studies that combined individual counseling with SMS reminders are described in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…Group counseling interventions were described in seven studies, five of which were conducted among adults [ 51 , 52 , 54 , 56 , 57 ] and two among adolescents [ 58 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of individuals speaking Telegu in the HIV+ group was significantly lower compared to the HIV− group, warranting cautious interpretation of the group differences in cognitive functioning. Other studies in different geographically/linguistically distinct regions of India have reported mild to moderate cognitive deficits in individuals with HIV-1 Clade C infection 11,12,24 . Our findings are consistent with prior reports of HIV-associated cognitive impairments in Clade C infected cohorts.…”
Section: Discussionmentioning
confidence: 86%
“…Our findings are consistent with prior reports of HIV-associated cognitive impairments in Clade C infected cohorts. Of note, these studies in Karnataka 12 , Chandigarh 24 , and Pune 11 , as well as our study in Chennai, vary in their study design (e.g., presence or absence of control group), HIV disease characteristics, and assessment approach (e.g., batteries and individual tests used, language of administration). Thus, direct comparisons across studies are not possible; however, there is evidence for a general trend of HIV-associated neurocognitive disorders in diverse Indian cohorts.…”
Section: Discussionmentioning
confidence: 94%